(untitled) (Dhaka University Journal of Science, 2021)
Children in slums are in a vulnerable situation because of their low living standard and poor access to healthcare services. It is melancholic that newborns are the worst victims of this devastating condition. This paper aims at finding out the potential determinants of neonatal death in urban slums using Bangladesh Urban Health Survey 2013 data. For the purpose of analyses, bivariate analysis has been conducted using chi-square test and multiple logistic regression model is used to assess the adjusted effects of potential determinants of neonatal mortality in slum area. Results indicate that type of birth, mother’s education, working status, NGO membership, migration status, pregnancy complication and water source played significant role in occurring neonatal death in slum areas. In order to reduce neonatal mortality in slums, migrant mothers should get the highest priority; awareness building programs should be held frequently in slums regarding maternal health and health care practices for the pregnant mothers as well as their newborn babies. Dhaka Univ. J. Sci. 69(1): 31-35, 2021 (January)